2022
DOI: 10.1186/s12957-022-02736-6
|View full text |Cite
|
Sign up to set email alerts
|

TIMM8A is associated with dysfunction of immune cell in BRCA and UCEC for predicting anti-PD-L1 therapy efficacy

Abstract: Background TIMM8A is a protein-coding gene located on the X chromosome. There is evidence that TIMM8A plays an important role in mitochondrial morphology and fission. Studies have shown that mitophagy and fission could affect the function of immune cells. However, there is currently no research on this gene’s role in cancer occurrence and progression. Methods TIMM8A expression was analyzed via the Tumor Immune Estimation Resource (TIMER) site and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…As the mutations of these two genes could be more helpful for immunotherapy prediction [ 29 , 30 ], the mutation frequencies of these two genes will be detected lately to more accurately evaluate their benefits in immunotherapy. Zhu et al showed that the poor treatment outcome of breast cancer may be due to the influence of MDSC and TAM in M2 [ 57 ]. In addition, there was also evidence that MDSC and TAM M2 limited the efficacy of anti-PD-L1 therapy in non-small cell lung cancer [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the mutations of these two genes could be more helpful for immunotherapy prediction [ 29 , 30 ], the mutation frequencies of these two genes will be detected lately to more accurately evaluate their benefits in immunotherapy. Zhu et al showed that the poor treatment outcome of breast cancer may be due to the influence of MDSC and TAM in M2 [ 57 ]. In addition, there was also evidence that MDSC and TAM M2 limited the efficacy of anti-PD-L1 therapy in non-small cell lung cancer [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The X chromosome protein-coding gene TIMM8A affects mitochondrial autophagy to influence immune infiltration and prognosis in UCEC ( 95 ). Enhanced chemodynamic therapy mediated by cancer-specific catalysts synergize with mitochondrial autophagy inhibition to improve endometrial cancer treatment efficacy ( 96 ).…”
Section: Cellular Organelle Mechanisms In Endometrial Cancer Pathogen...mentioning
confidence: 99%